Low-stress and high-stress singing have contrasting effects on glucocorticoid response - Fancourt, Daisy; Aufegger, Lisa; Williamon, Aaron (Frontiers in Psychology, 2015)
Performing music in public is widely recognised as a potentially stress-inducing activity. However, despite the interest in music performance as an acute psychosocial stressor, there has been relatively little research on the effects of public performance on the endocrine system. This study examined the impact of singing in a low-stress performance situation and a high-stress live concert on levels of glucocorticoids (cortisol and cortisone) in 15 professional singers. The results showed a significant decrease in both cortisol and cortisone across the low-stress condition, suggesting that singing in itself is a stress-reducing (and possibly health-promoting) activity, but significant increases across the high-stress condition. This is the first study to demonstrate that singing affects glucocorticoid responses and that these responses are modulated by the conditions of performance.